2005
DOI: 10.3758/cabn.5.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Personality from a controlled processing perspective: An fMRI study of neuroticism, extraversion, and self-consciousness

Abstract: Although neuroticism has been central to most theories of personality, self-reported neuroticism has had limited success in predicting expected behavioral outcomes. The reason for this may be due, in part, to the imprecision of self-reports. The purpose of this study was to examine the relationship between neural correlates of control systems and neuroticism, extraversion, and self-consciousness. In response to an oddball task, neuroticism was associated with increased dorsal anterior cingulate cortex (dACC) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
127
1
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(146 citation statements)
references
References 70 publications
14
127
1
4
Order By: Relevance
“…Therefore, one strategy to elucidate the neural substrate of neuroticism has been to study brain responses to negative affective (Canli, 2004) or conflicting (Eisenberger et al, 2005;Haas et al, 2007b) stimuli with noninvasive neuroimaging techniques. This work has begun to identify brain regions in which the amplitude of activation in response to negative (relative to neutral or positive) stimuli correlates significantly with neuroticism.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one strategy to elucidate the neural substrate of neuroticism has been to study brain responses to negative affective (Canli, 2004) or conflicting (Eisenberger et al, 2005;Haas et al, 2007b) stimuli with noninvasive neuroimaging techniques. This work has begun to identify brain regions in which the amplitude of activation in response to negative (relative to neutral or positive) stimuli correlates significantly with neuroticism.…”
Section: Introductionmentioning
confidence: 99%
“…In response to an inhibition task, self-reported More precisely, extraversion is negatively correlated with the activity of the PFC when the oddball trials are compared to the non-oddball trials in the inhibition task [8] .…”
Section: Fmrimentioning
confidence: 99%
“…1). E vidence from task-related neuroimaging revealed that extraversion is associated with activation in the p osterior cingulate/precuneus (PCC), medial prefrontal cortex (mPFC), dorsolateral prefrontal cortex (dlPFC), anterior cingulate cortex (A CC), middle temporal gyrus (MTG), the amygdala, and the nucleus accumbens [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations